Individuals' Unemployment Durations over the Business Cycle - Adriaan S. Kalwij (Institute for the Study of Labor (IZA), 2001)
Using a large panel of administrative records this study confirms the predictions of the ranking model of Blanchard and Diamond (1994) that an individual?s probability of leaving unemployment decreases with unemployment duration and increases with economic growth. However, the ranking model of Blanchard and Diamond (1994) makes the further prediction that negative genuine duration dependence will be stronger the more depressed the labour market. In conflict with this prediction this study provides persuasive empirical evidence that the pattern of negative genuine duration dependence does not change over the business cycle. Moreover it is shown that the finding in previous studies that negative genuine duration dependence becomes stronger the more depressed the labour market arises from failure to control for cyclical fluctuations in the composition of the newly unemployed. This finding carries a strong warning for policy assessment: unless controlled for cyclical fluctuations in the composition of the newly unemployed an evaluation of a policy designed to get the longterm unemployed into work will be biased towards a success in times of high economic growth and towards a failure in times of low economic growth.
Keywords: J64; C41; E32; 330; Unemployment; duration model; business cycles; Arbeitslosigkeit; Dauer; Langzeitarbeitslosigkeit; Konjunktur; Wirtschaftswachstum; Schätzung; Großbritannien